AdpAlin, a Pleiotropic Transcriptional Regulator, Is Involved in the Cascade Regulation of Lincomycin Biosynthesis in Streptomyces lincolnensis - Kang, Yajing; Wang, Yingying; Hou, Bingbing; Wang, Ruida; Ye, Jiang; Zhu, Xiaoyu; Wu, Haizhen; Zhang, Huizhan (Frontiers in Microbiology, 2019)
Lincomycin is one of the most important antibiotics in clinical practice. To further understand the regulatory mechanism on lincomycin biosynthesis, we investigated a pleiotropic transcriptional regulator AdpAlin in the lincomycin producer S. lincolnensis NRRL 2936. Deletion of adpAlin (which generated ΔadpAlin) interrupted lincomycin biosynthesis and impaired the morphological differentiation. We also found that putative AdpA binding sites were unusually scattered in the promoters of all the 8 putative operons in the lincomycin biosynthetic gene cluster (BGC). In ΔadpAlin, transcript levels of structural genes in 8 putative operons were decreased with varying degrees, and electrophoretic mobility shift assays (EMSAs) confirmed that AdpAlin activated the overall putative operons via directly binding to their promoter regions. Thus we speculated that the entire lincomycin biosynthesis is under the control of AdpAlin. Besides, AdpAlin participated in lincomycin biosynthesis by binding to the promoter of lmbU which encoded a CSR LmbU of lincomycin biosynthesis. Results of qRT-PCR and catechol dioxygenase activity assay showed that AdpAlin activated the transcription of lmbU. In addition, AdpAlin activated the transcription of the bldA by binding to its promoter, suggesting that AdpAlin indirectly participated in lincomycin biosynthesis and morphological differentiation. Uncommon but understandable, AdpAlin auto-activated its own transcription via binding to its own promoter region. In conclusion, we provided a molecular mechanism around the effect of AdpAlin on lincomycin biosynthesis in S. lincolnensis, and revealed a cascade regulation of lincomycin biosynthesis by AdpAlin, LmbU, and BldA.